INTERACTIVE VIDEO MAPPING IN THE INTERIOR DESIGN OF CATERING ESTABLISHMENTS: PRINCIPLES OF IMPLEMENTATION AND TECHNICAL PECULIARITIES - Брижаченко, Н. С.; Босий , І. М. (Art and Design, 2023)
The purposes of this study are to determine the principles of interactive video mapping implementation in the interior organization of catering establishments and outline the main technical advantages of projection systems. Methodology. To determine the main principles of interactive video mapping implementation in object-spatial environment it were used such theoretical methods of scientific research as analysis, systematization, method of work by analogy, comparison and generalization. The combination of these methods provides an opportunity to identify the main technical advantages of using video mapping in the interior design of public catering establishments. Results. The study considers interactive video projections and 3D-animations that became an important part in the interior design of public catering establishments. The analysis of the world design practice shows that the implementation of interactive video mapping in the internal space of restaurants and cafes realized by one of the three main principles: 1) the principle of dominance; 2) the principle of compositional equilibrium; 3) the principle of accent inclusion. The results of the research support the idea that in public interior design interactive video mapping have such technical peculiarities as: 1) the obligatoriness to place a multi-component software and hardware complex; 2) the possibility to create a projections on the surface of any curvature; 3) the capacity to project the image on the surface of any roughness; 4) the opportunity to use the projection systems where the application of sensory multimedia objects is impossible. It has been determined that the implementation of interactive video projections and 3D animation in the interior contributes to the creation of a visual lightness of space and is able to form a feeling of maximum immersion of a person in an illusory space. Scientific novelty. In the study it was determined the leading principles of implementation of interactive video mapping in the interiors of public catering establishments. The paper describes the technical features of the use of projection systems in interior design and identifies the main artistic effects created by means of video mapping. Practical significance. The results of the research can be used in the process of professional training in higher architectural and design educational institutions, in the development of new public interior projects or in the renovation of old buildings.